La comunità nei primi scritti di Troeltsch. La comunità con Dio e con gli altri - Cantillo, Giuseppe (Bollettino Filosofico, 2019)
This essay examines Ernst Troeltsch’s early writings on theology and philosophy of religion, with the aim of delineating the concept of “community” in the dual aspect of Gemeinde or religiöse Gemeinschaft and Gemeinschaft as a social and political community. The goal is to bring to the surface an idea of religion’s social function, central to Troeltsch’s theological and philosophical thought on Christianity, to which the most of his remarks are addressed. The research, which focuses in particular on Troeltsch’s long essay Die Selbständigkeit der Religion (1895-96) and the 1901 essay Leibniz und die Anfänge des Pietismus, underscores how from the idea of “communion with God” springs the idea of a non-authoritarian religious community, grounded on respect for the value of all believers, so as to minimize the separation between clergy and laity. The result is a democratic community, bound to have an impact on concepts such as society and political community. Keywords: Troeltsch, Theology, Religion, Christianity, Community